Guinea-Bissau : Request for Disbursement Under the Rapid Credit Facility-Staff Report; Press Release; and Statement by the Executive Director for Guinea-Bissau. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Guinea-Bissau's Request for Disbursement Under the Rapid Credit Facility (RCF). In 2012 and 2013, Guinea-Bissau suffered a severe balance of payments shock as the international price of raw cashew nuts-the main export product-fell by about 20 percent per year. The authorities have requested assistance under the RCF to help address the urgent balance of payments and fiscal financing needs for 2014. The IMF staff supports the authorities' request for assistance under the RCF in view of their currently limited capacity to implement policies of an upper credit tranche-quality economic program, the large and urgent balance of payments need, and the catalytic effect of IMF support for other external financing.